Spectroscopic Evidence of Intraband Gap States in α‐SnWO4 Photoanodes Introduced by Interface Oxidation. Issue 7 (29th January 2023) - Schnell, Patrick; Fernandez, Erwin; Obata, Keisuke; Rojas, Jennifer Velázquez; Favaro, Marco; Dittrich, Thomas; van de Krol, Roel; Abdi, Fatwa F.
Abstract : α ‐SnWO4 is an emerging photoelectrode material for photoelectrochemical water splitting, with several promising properties such as the favorable bandgap of 1.9 eV and suitable positions of the valence and conduction band. However, a major challenge remains: unprotected α ‐SnWO4 undergoes surface passivation that blocks further charge transfer, and α ‐SnWO4 electrodes that are covered with a protection/catalytic overlayer (e.g., NiO x, CoO x ) show limited photovoltage. Earlier studies reveal that interfacial oxidation occurs due to the deposition of the overlayer. This negatively impacts the photovoltage that can be extracted, which is attributed to Fermi‐level pinning at the interface. The exact origin of this Fermi‐level pinning mechanism, however, remains unclear. In the present study, a combination of surface photovoltage analysis and hard X‐ray photoelectron spectroscopy is used to elucidate the electronic structure of the α ‐SnWO4 /oxide interface. Both techniques offer compelling and consistent evidence for the presence of a defect state that is energetically located within the bandgap energy of α ‐SnWO4 and is likely responsible for the Fermi‐level pinning. Abstract : The deposition of overlayer on α ‐SnWO4 —a promising photoelectrode material for solar water splitting—improves its stability and catalytic activity but reduces the photovoltage. Here, complementary surface photovoltage and hard X‐ray photoelectron spectroscopy analyses show evidence for the presence of intrabandgap defect states at the α ‐SnWO4 /overlayer interface, which likely causes a Fermi‐level pinning and explains the photovoltage limitation.